Flood Risk Management at River Basin Scale : The Need to Adopt a Proactive Approach - Verwey, Adri (World Bank, Washington, DC, 2017)
This UFCOP Knowledge Note outlines key principles for flood risk management in river basins, that can be adapted for use by policymakers and project managers alike. It draws on a wide range of best practice case studies globally, where flood risk at the river basin scale has been well managed.